DETERMINANTS OF AUDIT QUALITY: THE EFFECT OF OWNERSHIP STRUCTURE AND AUDIT COMMITTEE ACTIVITIES - Agnes Silvia Ananda; Nurmadi Harsa Sumarta; Kingkin Kurnia Trio Satriya; Prihatnolo Gandhi Amidjaya (EKUITAS (Jurnal Ekonomi dan Keuangan), 2022)
This study examines the effect of ownership structure and audit committee activities on audit quality in Indonesian listed companies. The ownership structures studied consisted of managerial, institutional, government, foreign, and family ownership. The population of our study consists of 506 listed companies in Indonesian Stock Exchange between 2015 and 2020 with 317 total samples. Audit quality is proxied by the earnings surprise benchmark. Ownership structure is measured using the percentage of ownership. Audit committee activity is measured using the number of meetings held. Research data is analyzed with logistic regression analysis using SPSS statistic program. Our findings suggest that managerial, institutional, foreign, and family ownership as well as audit committee activities significantly affect audit quality while government ownership does not have significant effect. The findings of this research are designed to give information and feedback on the company's shareholders, assist the organization in delegating audit committee responsibilities, and provide readers with extra knowledge.